Contribution of suction on the stability of reinforced-soil retaining wall - Gofar, Nurly (2018)
Existing design methods of a reinforced-soil retaining wall were established for walls with cohesionless soil backfill. However, local soil has been used widely in the construction of such a wall for economic reasons. Laboratory and numerical studies have pointed out the merit of using cohesive backfill in association with geosynthetic reinforcement. Since the compacted soil was in an unsaturated condition during the construction of the reinforced wall, the apparent cohesion derived from both soil mineralogy and suction could contribute to the stability of the wall. This paper considers methods to include the suction contribution to the existing design guidelines based on slope stability analysis, i.e. simplified method and simplified stiffness method. The analyses were carried out on a case study of geosynthetics reinforced soil retaining wall. Results show that the contribution of suction as part of cohesion existing in the cohesive backfill could be considered for the stability analysis of reinforced soil retaining walls using the available design guidelines.